2010
DOI: 10.1089/end.2009.0307
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Haptic Feedback in Laparoscopic Training Using the LapMentor II

Abstract: The presence of HFB has less effect than it thought to be on the performance of the novice trainees. This may suggest that better HFB is still needed. However, there may be visual compensation for the lack of haptics. Playing videogames has a positive impact on economy, and the speed of the dominant had motion without affecting its accuracy. Further research is needed to clarify the value of haptics to the expert surgeon and compare it to the new trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 12 publications
(8 reference statements)
0
47
1
Order By: Relevance
“…One aspect offered by low-fidelity models that many VR simulators lack is tactile sensation. Minimally invasive VR simulators have been developed with simulated force feedback, adding approximately $20,000 to $30,000 to the price [5,6]. Despite the high additional cost, few studies have addressed the added value of this expensive feature.…”
mentioning
confidence: 99%
“…One aspect offered by low-fidelity models that many VR simulators lack is tactile sensation. Minimally invasive VR simulators have been developed with simulated force feedback, adding approximately $20,000 to $30,000 to the price [5,6]. Despite the high additional cost, few studies have addressed the added value of this expensive feature.…”
mentioning
confidence: 99%
“…This was attributed to the time commitment involved and the technical difficulty encountered by the participants. Although the incorporation of haptic technology increases the financial burden, no clear benefit with respect to training has been demonstrated (21,22). A systemic review (23) reported that although the majority of results show a positive advantage from haptic technology in MIS, interarticle consensus is neither absolute nor firm.…”
Section: Haptic Technologymentioning
confidence: 99%
“…However, problems remain with ensuring that simulation is realistic, affordable and has construct validity. Advances in virtual reality simulation have led to the development of built in resistance arms to provide haptic feedback [6]. While the technology has improved significantly over the years, problems remain with image production, poor trainer reviews and expense.…”
Section: Introductionmentioning
confidence: 99%